2010
DOI: 10.3961/jpmph.2010.43.5.423
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Catastrophic Health Expenditure on the Transition to Poverty and the Persistence of Poverty in South Korea

Abstract: 25.1% of the households in this study were found to be currently facing catastrophic health expenditure, and it was determined that catastrophic health expenditure is a cause of transition to poverty. This result shows that South Korea's health security system is not an effective social safety net. As such, to prevent catastrophic health expenditure and transition to poverty, the benefit coverage of South Korea's health security system needs to the strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 13 publications
(1 reference statement)
3
22
0
Order By: Relevance
“…These findings are in agreement with previous studies (Su et al, 2006;Kang, 2009;Song and Shin, 2010;Kavosi et al, 2012). Furthermore, Korea has a national health care system that is not connected to employment status, unlike countries such as the United States, where work decisions may be influenced by employment-connected health insurance.…”
Section: Discussionsupporting
confidence: 83%
“…These findings are in agreement with previous studies (Su et al, 2006;Kang, 2009;Song and Shin, 2010;Kavosi et al, 2012). Furthermore, Korea has a national health care system that is not connected to employment status, unlike countries such as the United States, where work decisions may be influenced by employment-connected health insurance.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have used a wide range of threshold criteria, ranging from 5 to 40 % of the household capacity, as the threshold value for defining CHE (Raban et al 2013;Van Minh et al 2013;Wagstaff and Van Doorslaer 2003;Xu et al 2003;Yardim et al 2010;Zhang et al 2010). The most commonly adopted thresholds were in a range from 10 to 40 % in the Korean studies (Kim and Yang 2009;Lee and Shin 2005;Shin et al 2010;Sohn et al 2010;Song and Shin 2010). Thus, to define CHE, thresholds ranging from 10 to 40 % were employed in this study.…”
Section: Catastrophic Health Expenditurementioning
confidence: 96%
“…(Available from http://english.mw.go.kr). J Fam Econ Iss (2015) 36:369-382 371 Lee and Shin 2005;Sohn et al 2010). Lee and Shin (2005) found that the likelihood of experiencing CHE was higher in the lower income groups and in the households with a greater number of elderly household members; the prevalence of CHE in the lowest income group was up to 1.4-2.0 times higher than that in the highest income group.…”
Section: Catastrophic Health Expenditure (Che) In South Koreamentioning
confidence: 97%
See 2 more Smart Citations